Alterations of white matter fractional anisotropy in unmedicated obsessive–compulsive disorder - Tao, Jiong (Neuropsychiatr Dis Treat, 2016)
BACKGROUND: Abnormalities in white matter (WM) have previously been reported in patients with obsessive–compulsive disorder (OCD). However, there was some inconsistency in the results obtained for altered regions of WM. The aim of this study was to investigate fractional anisotropy (FA) in the WM of the whole brain in patients with OCD by using diffusion tensor imaging (DTI). METHODS: In total, 28 unmedicated patients with OCD and 28 healthy volunteers underwent DTI scan. A voxel-based analysis was used to compare FA values in WM of the two groups at a voxel threshold of P<0.005 with an extent threshold of k>72 voxels (P<0.05; Alphasim correction). Subsequently, correlation analysis was conducted in order to find the correlation between the mean FA values in significantly altered brain regions and Yale–Brown Obsessive Compulsive Scale (Y-BOCS) scores of the OCD patients. RESULTS: Compared with healthy volunteers, the OCD patients had lower FA value in the left lingual gyrus, right midbrain, and right precuneus. There were no regions with significantly higher FA values in OCD patients compared with healthy volunteers. The mean FA values in the above regions (left lingual, r=0.019, P=0.923; right midbrain, r=−0.208, P=0.289; and right precuneus, r=−0.273, P=0.161) had no significant correlation with the Y-BOCS scores of the OCD patients. CONCLUSION: The findings of this study suggest that alterations in WM of the left lingual gyrus, right midbrain, and right precuneus are associated with the pathophysiology mechanism of OCD, and these microstructural alterations do not correlate with symptom severity of OCD.